Giving Effect to the Kyoto Mechanisms: Implications for South African Policy and Legislation - de Kock, Nicolette (Institute of Marine and Environmental Law, 2014)
This paper will incorporate a brief discussion of the science behind and the impacts of climate change, both globally and those impacts specific to South Africa. A brief history of the international climate change regime will follow. The primary focus is an examination of two of the three flexibility mechanisms under the Kyoto protocol, namely the Clean Development Mechanism (CDM) and Emissions Trading and their rules and guidelines for implementation. Regard will be had to specific emissions trading schemes as models for a future South African trading scheme and specific CDM projects currently under development in South Africa will be overviewed. Chapter three serves to analyse current policies and legislation in South Africa to determine the country's state of readiness to actively participate in the CDM and indirectly in emissions trading, so as to seize the numerous opportunities which are available to South Africa as a developing country. Finally some suggestions and recommendations are made as to the way forward, the positives and negatives of our current framework and the importance of capitalising on the significant advantages that effective participation in the CDM presents.